Morphology of the Myoepithelial Cell: Immunohistochemical Characterization from Resting to Motile Phase. (2nd July 2012) - Beha, Germana; Sarli, Giuseppe; Brunetti, Barbara; Sassi, Francesco; Ferrara, Domenico; Benazzi, Cinzia
Abstract : Myoepithelium is present in canine mammary tumors as resting and proliferative suprabasal and spindle and stellate interstitial cells. The aim of this paper was to evaluate a panel of markers for the identification of four different myoepithelial cell morphological types in the normal and neoplastic mammary gland and to investigate immunohistochemical changes from an epithelial to a mesenchymal phenotype. Cytokeratin 19 (CK19), cytokeratin 5/6 (CK5/6), cytokeratin 14 (CK14), estrogen receptor (ER), p63 protein, vimentin (VIM), and α -smooth muscle actin (Alpha-SMA) antibodies were used on 29 neoplasms (3 benign and 3 malignant myoepithelial tumors, 7 carcinomas in benign-mixed tumors and 16 complex carcinomas) and on normal tissue of mammary glands. All these antibodies were also tested on 3 mammary tissues from animals with no mammary pathology. The myoepithelial markers were well expressed in the suprabasal cells and gradually lost in the motile types, with the stellate cells maintaining only VIM expression typical of mesenchyma. ER labeled some resting and motile myoepithelial cells. On the basis of our results, we propose a transition from myoepithelial immotile cells into migratory fibroblast-like cells. This transition and the characterization of an immunohistochemical panel for resting and motile myoepithelial cells shed more light on the biological behavior of myoepithelial cells.